Dinamika Transfer Teknologi Solar Home System (SHS): Evaluasi atas“Uji Coba Penerapan Inovasi dan Teknologi SHS”di Kelompok Target untuk Kebijakan Pemasyarakatan Energi Terbarukan di Kota Kupang - Aprianus Ronny Paskal Modena (Jurnal Inovasi Kebijakan, 2018)
Most of SHS unit commersially available for household users are electronically designed to be as simple as plug and operate. However, technical and non-technical problems often arise, which could hamper the further wide-scale adoption of SHS in Kupang. Users are required to possess substantial knowledge and basic skill to operate and maintain SHS unit. In this paper, a review on current pilot project “Uji Coba Penerapan Inovasi dan Teknologi SHS” has been conducted to assess beneficiary’s level of acceptance; to explore the dynamic during the project; to assess the enabling factors and potential challenges faced by the SHS users in Kupang, East Nusa Tenggara. The new and completed concept of SHS adoption is introduced to assure the successful acceptance at ground level. Innovative financing options that support values awareness, acceptance, accesibility, and affordability should be incorporated to SHS implementation. Internal motivation and users characteristic might play an important role as enabling factors. Proximity distance between households and SHS dealers might act as inhibit factors. Thus, understanding enabling factors and inhibit factors is necessary for policy making process and further SHS introducing in Kupang.